Sharpness estimation in facial images by spectrum approximation. Issue 1 (January 2017) - Minin, Peter; Shumilov, Yury
Abstract This paper presents a novel approach to image sharpness assessment designed primarily for facial images. The approach can be described as holistic analysis of the frequency–amplitude spectrum by means of fitting an approximation model and obtaining the estimate based on the model's parameters. The proposed method shows better correlation with perceived sharpness than other existing methods both on synthetic tests and on a set of real-world face images. We demonstrate an application of the resulting estimate to enhance the accuracy of a face gender classifier.